The European Federation for Medicinal Chemistry (EFMC) Best Practice Initiative: Validating Chemical Probes. (3rd September 2020) - Quancard, Jean; Cox, Brian; Finsinger, Dirk; Guéret, Stéphanie M.; Hartung, Ingo V.; Koolman, Hannes F.; Messinger, Josef; Sbardella, Gianluca; Laufer, Stefan
Abstract: As part of an initiative aimed to share best practices in Medicinal Chemistry, the European Federation for Medicinal Chemistry (EFMC) is preparing a series of webinars and slide sets focused on the early phase of drug discovery. This educational material is freely accessible through the EFMC. The main target audiences are students or early career scientists and we also believe it will be valuable for experienced practitioners. The first of the series is focused on the generation and validation of high‐quality chemical probes, which are critical for drug discovery and more broadly to further our understanding of human biology and disease. Abstract : What are chemical probes and why are they important? Chemical probes are designed to selectively address a biological question; this is distinctly different from a drug, which is designed to produce a clinical outcome! Simple guidelines can be used to generate high‐quality chemical probes and obtain reliable data to further our understanding of human biology and disease.